Motivational reasons related to the practice of physical activity in the elderly - Pilot study to support strategies in primary health care in the municipality of Caicó (Research, Society and Development, 2021)
As we enter the 21st century, population aging has caused an increase in social and economic demands, and worldwide, the proportion of people aged 60 and over grows faster than that of any other age group. Physical activity is an important strategy for health promotion and brings numerous benefits, among them: greater longevity, reduced rates of morbidity and mortality, improved physiological capacity in patients with chronic diseases, in addition to psychological benefits. Based on these perspectives, this study aims to investigate the motivational reasons and possible factors related to the practice of physical activity in the elderly, and it becomes relevant because, in Brazil, there are still few studies addressing the motivations that lead elderly people to practice physical activity regularly. This is a pilot study, characterized as individualized, observational and cross-sectional. The data were collected in Basic Health Units of Primary Care in the municipality of Caicó (RN) from March to April 2020. This study involved the participation of 30 individuals aged 60 years or older, most of them female, and practitioners of light or moderate intensity activity. The most frequent comorbidities were: heart disease, hypertension and lung diseases. The motivational reasons that lead the elderly to practice physical activity were related to health, sociability and stress control, being less motivated by aesthetics and competitiveness.